Pengembangan Modul Pembelajaran Biologi Berbasis Potensi Lokal Danau Laut Tawar Takengon Ikan Depik (Rasbora Tawarensis) pada Materi Vertebrata - Annisa Apsari Anindita; Indayana Febriani Tanjung; Siti Maysarah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This study aims to determine the validity, practicality and effectiveness of biology learning modules based on local potential of Lake Laut Tawar Takengon Ikan Depik (Rasbora Tawarensis) on Vertebrate Material. This study used the Research and Development (R&D) research method based on the Thiagarajan methodology with four stages including define, design, devolepment and disseminate stages. This research was carried out from September to January 2022 with a sample of 26 students from SMA N 8 Takengon Unggul. The results showed that the biology learning module based on the local potential of Lake Laut Tawar Takengon Ikan Depik (Rasbora Tawarensis) is very suitable for use in learning. The validity test was tested by material experts and media experts. The material expert test was obtained by 81.37% and the media expert test was obtained by 81.25% and was included in the very feasible category to be used in learning. The practicality test was tested based on the responses of the biology teacher at SMA N 8 Takengeon Unggul and the responses of 26 students who were seen based on the response questionnaire sheet. The teacher's response test was obtained at 98.23% and the student's response test was 93.6% in the practical category used in the learning process. Testing the effectiveness of obtaining a score of 100% improves student learning outcomes during learning, this is evidenced by students' answers when tested based on the post-test questions given. So it can be concluded that the biology learning module based on local potential of Lake Laut Tawar Takengon Depik Fish (Rasbora Tawarensis) on Vertebrate Material is effective and appropriate for use in learning. Keywords: Module, Local Potential, Depik Fish